PROMISING AREAS FOR IMPROVING THE PERSONNEL MANAGEMENT MECHANISM - Z. M. Usmanova (European Science Publishing, 2024)
This article discusses the use of advanced techniques in order to improve the mechanism of personnel management in organizations and enterprises. The purpose of the study of personnel management at light industry enterprises is formulated taking into account the specifics of the industry and the characteristics of employees’ work. The paper presents a methodology for comparative analysis. When writing the article, methods of synthesis and generalization were used. The work provides a comparative analysis of personnel management, taking into account Japanese and South Korean experiences. The study provides recommendations for effective personnel management.
Keywords: personnel, enterprise, organization, management mechanism, management, personnel incentives, motivation, human potential, personnel policy, advanced techniques, Japanese experience, South Korean experience.